Berbagi suami atas nama Tuhan: pengalaman keseharian perempuan dipoligami di Langsa - Ansor, Muhammad (Sekolah Tinggi Agama Islam Negeri Salatiga, 2014)
This article explores how daily experience of the women living in the polygamous family in Langsa, Aceh. The primary argument proposed in this paper is that conflict, in fact, emerges from husband decision to practice polygamy in domestic life despite the belief of some women who accept that Islam countenances the practice of polygamy. The conflict sometimes arises among wives, between husband and the wives or among children of different wives. To prove such argument, the investigation of the daily experience of polygamous family such as the relation among the wives, household financial management, articulation of fairness on both physical and spiritual fulfilment, celebration of religious days (âIdul Fitri and âIdul Adha), as well as upbringing of children was carried out during second semester of 2011. The data was collected through semi-structured interview, observation to the domestic life of the polygamous family, and documentation on divorce suit as a result of practiced polygamy. This study revealed that peaceful family (keluarga sakinah) as often regarded as one of the ultimate goals of marriage would never be attained through such practice.